Resilience in the public healthcare supply chain: a theoretical framework for the Moroccan case against covid19 - Bouker Ben Aissa Ayman (African Scientific Journal, 2022)
The covid19 pandemic was an opportunity for the healthcare supply chain. The aim of the paper is to build a theoretical base for resilience aspects that should be considered by the Moroccan healthcare supply chain during pandemics